Gene expression of muscarinic, tachykinin, and purinergic receptors in porcine bladder: comparison with cultured cells - Bahadory, Forough; Moore, Kate H.; Liu, Lu; Burcher, Elizabeth (Frontiers in Pharmacology, 2013)
Urothelial cells, myofibroblasts, and smooth muscle cells are important cell types contributing to bladder function. Multiple receptors including muscarinic (M3/M5), tachykinin (NK1/NK2) and purinergic (P2X1/P2Y6) receptors are involved in bladder motor and sensory actions. Using female pig bladder, our aim was to differentiate between various cell types in bladder by genetic markers. We compared the molecular expression pattern between the fresh tissue layers and their cultured cell counterparts. We also examined responses to agonists for these receptors in cultured cells. Urothelial, suburothelial (myofibroblasts) and smooth muscle cells isolated from pig bladder were cultured (10-14 days) and identified by marker antibodies. Gene (mRNA) expression level was demonstrated by real-time PCR. The receptor expression pattern was very similar between suburothelium and detrusor, and higher than urothelium. The gene expression of all receptors decreased in culture compared with the fresh tissue, although the reduction in cultured urothelial cells appeared less significant compared to suburothelial and detrusor cells. Cultured myofibroblasts and detrusor cells did not contract in response to the agonists acetylcholine, neurokinin A and β,γ-MeATP, up to concentrations of 0.1 and 1 mM. The significant reduction of M3, NK2 and P2X1 receptors under culture conditions may be associated with the unresponsiveness of cultured suburothelial and detrusor cells to their respective agonists. These results suggest that under culture conditions, bladder cells lose the receptors that are involved in contraction, as this function is no longer required. The study provides further evidence that cultured cells do not necessarily mimic the actions exerted by intact tissues.